Evaluating the central and strategic role of Saka Kalpataru in successing of sustainable development - Listianto, Karunya Saka (Global and Policy Journal of International Relations, 2023)
The modern environmental conditions cannot be separated from climate change. Therefore, climate change is covered as one of the goals in the sustainable development agenda, titled "climate action". Theme for 2023 is "Human Impacts and Responsibility." Furthermore, Saka Kalpataru is a special unit within the Indonesian Scout movement that is engaged specifically in the environmental subject. Saka Kalpataru is valuable and crucial because it combines training, youth involvement, and collaboration with the Ministry of Environment and Forestry as well as the Ministry of Education as part of the Indonesian government. The activities completed by Saka Kalpataru enables and encourages young people to address environmental problems. These activities, which also collaborate with local communities, help promote several things regarding the climate change. Therefore, the central and strategic roles of Saka Kalpataru are fascinating to discover. This paper aims to evaluate Saka Kalpataru's activities with regard to the climate movement and the contribution to the success of sustainable development.DOI: https://doi.org/10.33005/jgp.v11i02.4139